2019
DOI: 10.2217/bmm-2018-0306
|View full text |Cite
|
Sign up to set email alerts
|

Association Between AXIN1 Gene Polymorphisms and Epithelial Ovarian Cancer in Chinese Population

Abstract: The study was aimed to explore the association between AXIN1 gene polymorphism and epithelial ovarian cancer (EOC) susceptibility as well as prognosis. Methods: A total of 165 EOC cases and 327 healthy controls were recruited to participate in this study. In total three tag SNPs in AXIN1 gene were genotyped using PCR-restriction fragment length polymorphism. Results: Significantly increased EOC risk was found associated with the A/C heterozygous genotype of rs12921862, the C allele and C/T genotype in the rs18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The overwhelming majority of selected biomarker studies investigated different tissue-based biomarkers using a variety of technical research methods. The selected tissue prognostic biomarkers can be divided into immunohistochemical biomarkers (68.77%) , DNA biomarkers (3.95%) [159,[233][234][235][236][237][238][239][240][241] and RNA biomarkers (27.28%) . The prognostic value of 172 protein biomarkers was evaluated by immunohistochemistry in 174 studies (Table 2).…”
Section: Tissue-based Prognostic Biomarkersmentioning
confidence: 99%
“…The overwhelming majority of selected biomarker studies investigated different tissue-based biomarkers using a variety of technical research methods. The selected tissue prognostic biomarkers can be divided into immunohistochemical biomarkers (68.77%) , DNA biomarkers (3.95%) [159,[233][234][235][236][237][238][239][240][241] and RNA biomarkers (27.28%) . The prognostic value of 172 protein biomarkers was evaluated by immunohistochemistry in 174 studies (Table 2).…”
Section: Tissue-based Prognostic Biomarkersmentioning
confidence: 99%
“…Zhang et al indicated the effects of rs12921862 AC and the rs1805105 GA genotypes on epithelial ovarian cancer (EOC) susceptibility. In addition, they showed that EOC patients with rs12921862 CC genotype improved by the Kaplan–Meier survival curves for the overall survival 27 . In a meta‐analysis performed on eight studies on the association between AXIN2 rs2240308 polymorphism and overall cancer risk (2015), Gong et al showed decreased cancer risk in the homozygous, heterozygous, dominant, and allelic (T vs. C) models 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they showed that EOC patients with rs12921862 CC genotype improved by the Kaplan-Meier survival curves for the overall survival. 27 In a meta-analysis performed on eight studies on the association between AXIN2 rs2240308 polymorphism and overall cancer risk (2015), Gong et al showed decreased cancer risk in the homozygous, heterozygous, dominant, and allelic (T vs. C) models. 28 Similar to the finding of the present study, Pu et al showed an increased risk of cell renal cell carcinoma (ccRCC) in individuals carrying rs1805105 GA/GG genotypes and rs12921862 AA genotype.…”
Section: Discussionmentioning
confidence: 99%